Percutaneous venting gastrostomy/gastrojejunostomy for malignant bowel obstruction: a qualitative study. Issue Volume 9: Issue (2019)Supplement 4 (9th October 2019) - Singh Curry, Rebecca; Evans, Elizabeth; Raftery, Anne-Marie; Hiscock, Julia; Poolman, Marlise
Abstract : Objective: Malignant bowel obstruction (MBO) is a complication of advanced malignancy and is associated with a short prognosis. MBO can infrequently be reversed by surgery or stenting. The focus of treatment is usually symptomatic management, of which percutaneous venting gastrostomy/gastrojejunostomy (PVG) is one consideration. There is little data considering the impact of PVG on quality of life; we therefore aimed to explore this. Methods: We identified patients with a PVG inserted for MBO and those who consented to participate were interviewed. The interviews were audio recorded, transcribed and analysed using Framework. Alongside patient interviews, a data collection tool was designed and used to record patient demographics and medical information, enabling us to contextualise individual patients' experiences. Results: 11 patients were interviewed and 10 patients' data were analysed (1 patient withdrew). No patients regretted having a PVG and many benefitted symptomatically and psychosocially. Challenges encountered included practical issues, pain and PVG tube complications. Conclusions: The analysis provided a detailed insight into the impact of PVG insertion and demonstrated that each patient's experience is shaped by a complex interplay of individual factors, thereby highlighting the need to improve referral criteria and individualise patient selection. Other service improvements include enhancing information provision for patients and training for healthcare professionals, thus aiming to mitigate the challenges experienced. Our study is the first in-depth exploration of patients' experiences of PVG at a tertiary cancer centre. Ensuring that the insights from this study are fed back to guide future service provision is critical in enhancing future patient experiences.